PERAN EDUKASI MODERNISASI SOSIAL DALAM MEMBENTUK GENERASI DIGITAL YANG RUKUN DI SDN 01 DAN 03 HALABAN - Rosmi Eni; Ciptati Handayani; Syifa Reihanny; Azizah Rihadatul Aisya; Abdul Roziq; Diva Ananda Mareta; Ahmad Deby Fahrezi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This community service activity aims to analyze the role of social modernization education in shaping a harmonious digital generation at SDN 01 and SDN 03 Halaban. The background of this activity is based on the increasing use of digital technology among students, which has not been fully accompanied by adequate understanding of digital ethics and proper social interaction. The method used is Participatory Action Research (PAR), consisting of stages of problem identification, planning, action implementation, as well as observation and evaluation. Data collection techniques include observation, interviews, and documentation. The results of the activity indicate that social modernization education implemented through digital literacy, character education, and interactive activities is able to improve students’ understanding and social behavior. Positive changes are reflected in increased mutual respect, improved collaboration skills, and greater awareness in using digital technology wisely. The active involvement of teachers and the support of parents through digital parenting further strengthen the success of the program. Thus, the PAR approach in social modernization education has proven to be effective in shaping a digital generation that is not only technologically competent but also harmonious, tolerant, and socially responsible.